If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(-4)=-6-(-4)/(-3)-(-6)(Y-(-2))
We move all terms to the left:
-(-4)-(-6-(-4)/(-3)-(-6)(Y-(-2)))=0
Domain of the equation: (-3)-(-6)(Y-(-2)))!=0We add all the numbers together, and all the variables
Y∈R
-(-6-(-4)/(-3)-(-6)(Y-(-2)))+4=0
We multiply all the terms by the denominator
-(-6-(-4)+4*(-3)-(-6)(Y-(-2)))=0
We calculate terms in parentheses: -(-6-(-4)+4*(-3)-(-6)(Y-(-2))), so:We get rid of parentheses
-6-(-4)+4*(-3)-(-6)(Y-(-2))
determiningTheFunctionDomain -(-6)(Y-(-2))-6-(-4)+4*(-3)
We add all the numbers together, and all the variables
-(-6)(Y-(-2))-14
We calculate terms in parentheses: -(-6)(Y-(-2)), so:We multiply parentheses ..
-6)(Y-(-2)
We add all the numbers together, and all the variables
-6)(Y+2
Back to the equation:
-(-6)(Y+2)
-(-6Y-12)-14
We get rid of parentheses
6Y+12-14
We add all the numbers together, and all the variables
6Y-2
Back to the equation:
-(6Y-2)
-6Y+2=0
We move all terms containing Y to the left, all other terms to the right
-6Y=-2
Y=-2/-6
Y=1/3
| -3(x+3)=-5x-15-4x | | (-19)+x=(+14) | | -4m+8=-20 | | 2/5=x/6.5 | | (9^12)(6^y)=(2*81)^12 | | x/3+2=11, | | 3x+50=0 | | x+(-29)=15 | | 4(k-8)=-32$4k | | (2x+1)/(7x-10)=0 | | +7)-14-8x=-2(-3x+7) | | (4x-3)•5-6x=-4(5+9x) | | 3p²+7p+14=0 | | 5xx-12=40 | | x^2-1=1.89 | | x^+1=2.89 | | 5^x=1÷625 | | 5x=1÷625 | | a²=-6a-7 | | x(4-x)=1 | | 0=20x^2-12x-9 | | 3=0*2+c | | (3x-6)(2x+9)=0 | | 3x²21-6=0 | | 3x²-21-6=0 | | 52-x=3x | | x^+50x+625=0 | | 4^x-0.5-35^x+8=0 | | 5k^2-17k+22=0 | | 4^x-0.5-34x+8=0 | | 5x+6=-8x+7 | | 4/x+5=0 |